Reconstitution of the Vital Functions of Munc18 and Munc13 in Neurotransmitter Release - Ma, Cong (2012)
Neurotransmitter release depends critically on Munc18-1, Munc13, the Ca(2+) sensor synaptotagmin-1 and the SNAREs syntaxin-1, synaptobrevin and SNAP-25. In-vitro reconstitutions have shown that syntaxin-1-SNAP-25-liposomes fuse efficiently with synaptobrevin-liposomes in the presence of synaptotagmin-1-Ca(2+), but neurotransmitter release also requires Munc18-1 and Munc13 in vivo. Here we found that Munc18-1 could displace SNAP-25 from syntaxin-1 and that fusion of syntaxin-1-Munc18-1-liposomes with synaptobrevin-liposomes required Munc13, in addition to SNAP-25 and synaptotagmin-1-Ca(2+). Moreover, when starting with syntaxin-1-SNAP-25 liposomes, NSF-α-SNAP disassembled the syntaxin-1-SNAP-25 heterodimers and abrogated fusion, which then required Munc18-1 and Munc13. We propose that fusion does not proceed through syntaxin-1-SNAP-25 heterodimers, but starts with the syntaxin-1-Munc18-1 complex; Munc18-1 and Munc13 then orchestrate membrane fusion together with the SNAREs and synaptotagmin-1-Ca(2+) in an NSF- and SNAP-resistant manner.